Androgen-Receptor Positive Lacrimal Sac Adenocarcinoma Demonstrating Long-Lasting Response to LHRH Analog Plus Abiraterone Treatment - Vagia, Elena; Economopoulou, Panagiota; Oikonomopoulos, Nikolaos; Athanasiadis, Ilias; Dimitriadis, George; Psyrri, Amanda (Frontiers in Oncology, 2015)
Tumors arising at the lacrimal sac are extremely rare, as a limited number of cases have been reported worldwide. They are commonly primary and the majority of them are malignant and epithelial in origin. Adenocarcinomas account for a small percentage of these tumors. Treatment of local disease mainly includes complete surgical resection. However, metastatic disease has a poor prognosis and the development of new treatment strategies is highly important. Research efforts mainly focus on the identification of molecular targets for therapy. Herein, we describe for the first time a case of a patient with an Androgen Receptor expressing adenocarcinoma of the lacrimal sac that had an impressive response to abiraterone.